General measures and supportive therapy for pulmonary arterial hypertension: updated recommendations from the Cologne Consensus Conference 2018 - Grünig, Ekkehard; Benjamin, Nicola; Harutyunova, Satenik; Marra, Alberto M. (International journal of cardiology, 2018)
In the summer of 2016, delegates from the German Respiratory Society, the German Society of Cardiology and the German Society of Pediatric Cardiology met in Cologne, Germany, to define consensus-based practice recommendations for the management of patients with pulmonary arterial hypertension (PAH). These recommendations were built on the 2015 European Pulmonary Hypertension guidelines aiming at their practical implementation, considering country-specific issues, and including new evidence, where available. To this end, a number of working groups was initiated, one of which was specifically dedicated to general measures (i.e. physical activity/supervised rehabilitation, pregnancy/contraception, elective surgery, infection prevention, psychological support, travel) and supportive therapy (i.e. anticoagulants, diuretics, oxygen, cardiovascular medications, anaemia/iron deficiency, arrhythmias) for PAH. While the European guidelines provide detailed recommendations for the use of targeted PAH therapies as well as supportive care, detailed treatment decisions in routine clinical care may be challenging, and the relevance of supportive care is often not sufficiently considered. In addition, new evidence became available, thus requiring a thorough reevaluation of specific recommendations. The detailed results and recommendations of the working group on general measures and supportive therapy for PAH, which were last updated in the spring of 2018, are summarized in this article.